A Strategic Asset Pricing Model for Relative Performance Concern. Issue 8 (3rd August 2017) - Yu, Jianfeng; Xu, Weidong
ABSTRACT: We propose a strategic asset pricing model for the relative performance concern with heterogeneous beliefs in the framework of Nash equilibrium. In our model, the presence of heterogeneous beliefs generates the upward pressure on the stock market volatility and gives rise to the separation of agents' perceived Sharpe ratios. We show that if one of the agents temporarily wins the market, the presence of relative performance concern will reduce the impacts of the winner and make the investors who have been edged out of the market more inclined to return. Besides, the sufficiently strong concern of relative performance will bring investors the extreme aversion to losing and get them to trade similarly.